Konsep Infrastruktur Hijau Pada Area Khatulistiwa Park Kota Pontianak - Setiyono, Setiyono; Sidiq, Akhmad (JU-ke: Jurnal Ketahanan Pangan, 2018)
Climate change due to increasing global warming demands human habits to change. Eco-friendly lifestyles are being implemented in some countries as well as in Indonesia. Evidenced by the start popping up environmentally friendly buildings and green open areas. This study examines the elements of green infrastructure at Khatulistiwa Park Pontianak City which includes appropriate land use, source and material cycle, health and comfort of space, management and building environment. Khatulistiwa Park as a conservation area of endemic plants, typical culinary Pontianak and West Kalimantan is very precisely built in the area of Tugu Khatulistiwa which is one of the historic buildings as an icon of Pontianak City. Use of building materials on the Khatulistiwa Park should pay attention to the impression and character that want to be displayed in the building view because the selection of materials will directly show the texture of the display. A shady environment with many plants around will lower the temperature of the area. Preparation of heat shading which serves as a heat retention fins. Access to the Equator Park area can use most of the land transportation in the form of motorbikes, cars, public transport and taxis, also accessible via water transportation.